Cigarette Smoking and Incident Heart Failure: Insights From the Jackson Heart Study. Issue 24 (12th June 2018) - Kamimura, Daisuke; Cain, Loretta R.; Mentz, Robert J.; White, Wendy B.; Blaha, Michael J.; DeFilippis, Andrew P.; Fox, Ervin R.; Rodriguez, Carlos J.; Keith, Rachel J.; Benjamin, Emelia J.; Butler, Javed; Bhatnagar, Aruni; et al.
Abstract : Background: Cigarette smoking has been linked with several factors associated with cardiac dysfunction. We hypothesized that cigarette smoking is associated with left ventricular (LV) structure and function, and incident heart failure (HF) hospitalization. Methods: We investigated 4129 (never smoker n=2884, current smoker n=503, and former smoker n=742) black participants (mean age, 54 years; 63% women) without a history of HF or coronary heart disease at baseline in the Jackson Heart Study. We examined the relationships between cigarette smoking and LV structure and function by using cardiac magnetic resonance imaging among 1092 participants, cigarette smoking and brain natriuretic peptide levels among 3325 participants, and incident HF hospitalization among 3633 participants with complete data. Results: After adjustment for confounding factors, current smoking was associated with higher mean LV mass index and lower mean LV circumferential strain ( P <0.05, for both) in comparison with never smoking. Smoking status, intensity, and burden were associated with higher mean brain natriuretic peptide levels (all P <0.05). Over 8.0 years (7.7–8.0) median follow-up, there were 147 incident HF hospitalizations. After adjustment for traditional risk factors and incident coronary heart disease, current smoking (hazard ratio, 2.82; 95% confidence interval, 1.71–4.64), smoking intensity among current smokers (≥20 cigarettes/d: hazard ratio, 3.48; 95% confidence interval, 1.65–7.32), and smoking burden among ever smokers (≥15 pack-years: hazard ratio, 2.06; 95% confidence interval, 1.29–3.3) were significantly associated with incident HF hospitalization in comparison with never smoking. Conclusions: In blacks, cigarette smoking is an important risk factor for LV hypertrophy, systolic dysfunction, and incident HF hospitalization even after adjusting for effects on coronary heart disease. Abstract : Supplemental Digital Content is available in the text.